2020
DOI: 10.1371/journal.pone.0231779
|View full text |Cite
|
Sign up to set email alerts
|

How do perceived and objective measures of neighbourhood disadvantage vary over time? Results from a prospective-longitudinal study in the UK with implications for longitudinal research on neighbourhood effects on health

Abstract: Background Theories of health outcomes often hypothesize that living in more socially and economically disadvantaged neighbourhoods will lead to worse health. Multiple measures of neighbourhood disadvantage are available to researchers, which may serve as better or worse proxies for each other across time. To inform longitudinal study design and interpretation we investigated how perceived and objective measures of neighbourhood disadvantage vary over time and the factors underlying this variation. Methods Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Subjective and objective measures of health outcomes and environmental exposure are worth considering separately, since they often assess different, yet overlapping, concepts, and they each have advantages and limitations. Subjective and objective environmental measures can also point toward distinct intervention and policy responses [ 99 , 100 ]. Subjective measures included those that were self-reported by participants or their parents (e.g., self-reported mental health or perceived neighborhood safety), while objective measures were based on diagnostic data or administrative and third-party data usually handled within geographic information systems (GIS) (e.g., greenspace coverage).…”
Section: Resultsmentioning
confidence: 99%
“…Subjective and objective measures of health outcomes and environmental exposure are worth considering separately, since they often assess different, yet overlapping, concepts, and they each have advantages and limitations. Subjective and objective environmental measures can also point toward distinct intervention and policy responses [ 99 , 100 ]. Subjective measures included those that were self-reported by participants or their parents (e.g., self-reported mental health or perceived neighborhood safety), while objective measures were based on diagnostic data or administrative and third-party data usually handled within geographic information systems (GIS) (e.g., greenspace coverage).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to previous studies (Zhang et al, 2019), we found that objective measures of neighbourhoods were somewhat more strongly associated with higher levels of stress than subjective measures. Yakubovich et al (2020) highlight that ecological measures should not be inferred as a definitive marker that neighbourhood characteristics Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…Worsening neighbourhood factors, including crime and disorder, social environment, and physical environmental factors, have also been associated with increased anxiety and depression scores (Olsen et al, 2017). Subjective neighbourhood environment measures are based on residents' perceptions and assessment of neighbourhood features (Zhang et al, 2019) and include, for example, individual assessments of neighbourhood quality, neighbourhood stress, safety, and social cohesion (Yakubovich et al, 2020). Objective neighbourhood environment measures may be derived from secondary or spatial datasets to provide neighbourhood context (Zhang et al, 2019), and typically include deprivation and crime statistics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective measures are not simply proxies of objective measures or vice versa. It can be argued that objective measures of the neighbourhood do not capture experienti al or relational aspects which are often important for understanding relationships and mechanisms of neighbourhood effects on health (Yakubovich, Heron and Humphreys, 2020). Subjective measures of the neighbourhood environment reflect an individual’s experience of their surroundings and allow residents to report on the neighbourhood social context not possible with objective measures, although there may be limitations that have to do with how neighbourhood is defined (Corcoran et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%